Eugenia ruschiana (Myrtaceae), a new species from southeastern Brazilian Atlantic forest - Bünger, Mariana De Oliveira; Mazine, Fiorella Fernanda; Stehmann, João Renato (Phytotaxa, 2016)
Eugenia ruschiana, collected in the montane Atlantic forest of Espírito Santo state, is described, illustrated and compared with E. itacarensis, from which it differs mostly through the smaller size and shape of the bracteoles and calyx lobes, as well as, by its distinct geographic distribution. We also assess its conservation status and the species was considered endangered.